What Went Wrong? The Downfall of Arthur Andersen and the Construction of Controllability Boundaries Surrounding Financial Auditing* - Gendron, Yves; Spira, Laura F. (Contemporary Accounting Research, 2009)
This paper provides insights into the dynamics underlying the construction of controllability boundaries surrounding the financial audit function, through an analysis of the sensemaking narratives of former members of Arthur Andersen reflecting upon the collapse of their firm. Our focus is how members, in light of their firm’s downfall, assess the abilities of public accounting firms to control financial audit work and auditor behaviour (i.e., organizational controllability), and the abilities of outside, non-accounting bodies to regulate financial auditing (i.e., regulatory controllability). The investigation is predicated on interviews with twenty-five former partners and employees of Arthur Andersen, mostly in Canada and the United Kingdom. Our qualitative analysis indicates that a majority of interviewees adheres to the view that financial auditing can best be controlled via a network of bureaucratic and clan controls established within accounting firm organizations, without any direct involvement from the part of regulators. A number of interviewees, though, consider that a reinforcement of outside regulation is necessary to discipline financial auditors. In spite of these differences, the vast majority of interviewees consider that financial auditing is controllable (via organizational or regulatory control), which is of interest given their spatial and emotional proximity from the controversial collapse of their firm. Also, most participants do not see the professional association as a useful or relevant party in helping the professional accounting community manoeuvring in times of turmoil. Important governance issues, ensuing from our analysis, are discussed.